A LITERATURE STUDY ON DIGITAL MARKETING STRATEGIES IN INCREASING SALES - Suadi Sapta Putra; Resti Hardini; Rahayu Lestari; Kumba Digdowiseiso; Juhaizi Mohd Yusof (RADJA PUBLIKA, 2024)
The rapid advancement of digital technology has led to the emergence of digital marketing as a fundamental aspect of the business world. It refers to a range of marketing strategies commonly employed by companies and other business entities nowadays to efficiently and economically promote their products. Employing digital technology in marketing is regarded as a more effective method for enhancing sales in companies or business entities. Sales are vital for ensuring the operational sustainability of the company, funding investments, and meeting financial obligations. Inadequate sales performance can subject a company to the peril of heightened credit risk and potential bankruptcy. This study utilizes a systematic literature review (SLR) approach to evaluate the efficacy of digital marketing strategies in improving sales. The researcher conducted a comprehensive analysis of 18 pertinent literature studies, scrutinizing them in relation to three specific research questions. The findings indicate that digital marketing has the potential to enhance sales for companies or business entities.